The Effects of Counseling on The Knowledge and Attitude About The Risking Sexual Behavior of SMA 5 and SMA 21 Students in Makassar City - Elna Sari; Andi Zulkifli; Suriah (Universitas Mandala Waluya, 2021)
SMA 5 and SMA 21 are the leading schools in Makassar City which have a Youth Counseling Information Center. Previous research looked at the influence of game simulation and brainstorming on the knowledge and attitudes of stundent about reproductive health for high school adolescents in Makassar City, including SMA 5 and SMA 21, but the results did not have effect on students' knowledge and attitudes. Therefore, the researcher took the initiative to provide another intervention in the form of counseling. This study aims to determine the effect of counseling on knowledge and attitudes about risky sexual behavior among students in SMA 5 and SMA 21 Makassar City. This study used a quasi-experimental design with a randomized pre test post test control group design. A sample of 76 students of class XI SMA 5 and SMA 21 Makassar City, using simple random sampling technique. Data collection was using a questionnaire. Statistical analysis used paired t-test and independent samples t-test. The results showed that there was an effect of counseling on knowledge (p = 0.002) but there was no effect on attitudes (p = 0.865) in SMA 5 and SMA 21 Makassar City. It is suggested that SMA 5 and SMA 21 Makassar City be active in conducting counseling, especially counseling about attitudes, so that students have positive attitudes about risky sexual behavior.